The Source Of Error in Translation - Munawir (Inspiring: English Education Journal, 2021)
Based on the preliminary study, most students made error in writing abstract especially in translating Indonesian language into English language. Therefore, the aim of this research was to find out the sources of translation error and the dominant of source of error. This research used a descriptive method. In getting the data, this research applied a purposive sampling technique and the data of this research was taken secretly. The subject of this research was 61 abstracts of theses and dissertation taken from various universities in Makassar and analyzed by using error analysis technique. The result of the research showed that in the sources of translation error, the most error made by the students was Syntactic with 120 errors (62.1%) Lexical with 42 errors (21.7%), Unclassified with 17 errors (8.8%), and the least was Morphological aspect with 14 errors (7.2%). It can be concluded that the dominant source of error was the syntactic aspect.